2022
DOI: 10.3390/coatings12010077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multi-Walled CNT Incorporation on Dielectric Properties of PVDF-BaTiO3 Nanocomposites and Their Energy Harvesting Possibilities

Abstract: The current study investigated the fabrication of multi-walled carbon nanotubes (MWCNTs) adhering to Barium titanate (BaTiO3) nanoparticles and poly(vinylidene fluoride) (PVDF) nanocomposites, as well as the impact of MWCNT on the PVDF-BaTiO3 matrix in terms of dielectric constant and dielectric loss with a view to develop a high performance piezoelectric energy harvester in future. The capacity and potential of as-prepared nanocomposite films for the fabrication of high-performance flexible piezoelectric nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…[ 21 ] As can be seen from Table 4, both series of TPU films exhibited reduced dielectric losses with the addition of BT, however, lower values were found for TPU films with modified fillers, which indicated that the incorporation of a specific quantity of MWCNT f can increase the dielectric constant and decrease the loss tangent. [ 5,24 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] As can be seen from Table 4, both series of TPU films exhibited reduced dielectric losses with the addition of BT, however, lower values were found for TPU films with modified fillers, which indicated that the incorporation of a specific quantity of MWCNT f can increase the dielectric constant and decrease the loss tangent. [ 5,24 ]…”
Section: Resultsmentioning
confidence: 99%
“…[21] As can be seen from Table 4, both series of TPU films exhibited reduced dielectric losses with the addition of BT, however, lower values were found for TPU films with modified fillers, which indicated that the incorporation of a specific quantity of MWCNT f can increase the dielectric constant and decrease the loss tangent. [5,24] One of the basic requirements for the application of dielectric materials in capacitors is to possess resistivity to higher electric fields. To examine this behavior, the dielectric breakdown strength (E b ) of the TPU composite films was analyzed by measuring the breakdown voltage.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
“…The aggregation of CNT does not easily maintain the nature of high aspect ratio and thus the polarization efficiency decreases . Moreover, we compared with other PVDF based piezoelectric materials (PVDF/PDMS, PVDF/CNT, PVDF-TrFE, PVDF/P-CNT, PVDF/IL, PVDF/PMMA, PVDF/BaTiO3/MWCNT, PVDF/BTO, PVDF/MWCNT and PVDF/TrFE) as shown in Figure g. Our PVDF/CNT scaffold exhibited high beta crystal content, good mechanical property, and competitive output capability.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF/ CNT, 21 PVDF-TrFE, 61 PVDF/P-CNT,62 PVDF/IL,63 PVDF/ PMMA,64 PVDF/BaTiO3/MWCNT,65 PVDF/BTO,66 PVDF/MWCNT67 and PVDF/TrFE 68 ) as shown in Figure5g. Our PVDF/CNT scaffold exhibited high beta crystal content, good mechanical property, and competitive output capability.…”
mentioning
confidence: 95%
“…As can be seen in Figure 14 a, the piezoelectric coefficient d 33 of the composite BT-PDMS films significantly increased after the poling process for all studied BT concentrations between 10 and 40 wt.% [ 63 ]. Moreover, in cases using piezoelectric PVDF polymer together with BT nanomaterials, the poling process is quite important, because during the poling the extent of the most piezoelectrically active β -phase of PVDF significantly increased, as reported by Zhao et al ( Figure 14 b) [ 38 ], and has strong influence on the output results [ 70 ].…”
Section: Parameters Affecting Output Performance Of P-ngmentioning
confidence: 99%